Economic Analysis of Para-wilt Management in Bt Cotton (Gossypium hirsutum L.) in Mansa District of South-western Punjab, India - Singh, Gurdeep; Singh, Pritpal; Singh, Kulwant; Sodhi, Gurjinder Pal Singh; Sekhon, Bhallan Singh (Indian Journal of Extension Education, 2021)
Parawilt characterized by a sudden drooping of leaves followed by death of plants within few hours after rainfall or heavy irrigation has been the major physiological disorder affecting productivity of Bt-Cotton (Gossypium hirsutum L.). We studied the effect of foliar application of cobalt chloride (@10 mg L-1 water) within 24-36 hours after appearance of symptoms on recovery rate, seed cotton yield and economics at farmers’ fields in Mansa district of south-western Punjab. The results of front line demonstrations revealed that foliar application of cobalt chloride resulted in significantly (p